Clinical Outcomes of the Dynamic Lumbar Pedicle Screw-rod Stabilization: 2-Year Follow-up Results. Issue 3 (August 2016) - Wang, Chao-Jan; Graf, Henry; Wei, Hung-Wen
Abstract : This study included 67 patients who underwent dynamic stabilization of the lumbar spine with the polyetheretherketone (PEEK) and Ti-alloy-cable composite. Patient participation was based on the presence of degenerative spondylolisthesis (grade I), lateral or central spinal stenosis, and their physician's recommendation that the patient required decompression and instrumented fusion for 1 or 2 contiguous spinal levels between L1 and S1. Participants were evaluated preoperatively and postoperatively at 3, 6, 12, and 24 months. The ratio of intervertebral disk space to vertebral body height (IVS) and segmental and lumbar lordosis were evaluated preoperatively and postoperatively. Pain scores were evaluated by Visual Analog Scale (VAS) and Oswestry Disability Index (ODI) preoperatively and postoperatively. The mean pain and function scores improved significantly from the baseline to 24-month follow-up evaluation, as follows: ODI score from 53.4% to 27.3% and back pain VAS from 63.2 to 31.9. The ODI and VAS scores decreased significantly from preoperative to postoperative. The IVS ratio remained unchanged between preoperative and postoperative conditions. The lumbar and segmental lordotic angles increased insignificantly from preoperative levels in the months following surgery. In conclusions, the early clinical outcomes of treatment with the dynamic rod composed of PEEK and Ti-alloy cable are promising in terms of maintenance of segmental lordosis and intervertebral space ratio, and improvement in pain and disability. Future clinical studies would be needed to examine and provide information regarding the impact of this dynamic pedicle screw system on the incidence of adjacent-level disease.